1974
DOI: 10.1002/jez.1401870306
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of the crowding factor from Carassius auratus and Cyprinus carpio

Abstract: Crowding factors are those substances released by fish, which, under crowded conditions, inhibit both their growth and reproduction and depress their heart rate. We have partially purified the crowding factor from goldfish and carp by following a heart-rate-depression assay. The heart-rate-depression activity eluted with the diglyceride fraction from both silicic acid pnd Sephedex LH-20. A slightly different activity eluted with the free sterols. The peak activity associated with the diglycerides has a distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Whilst it is too early to draw any firm conclusions as to the physiological importance of elevated GH during crowding stress it is possible that elevations in GH is a short term protective response against limited oxygen availability during crowding stress. In addition, the role and importance of ''crowding factors'' that are chemical agents (pheromones) known to adversely affect growth of fish (Francis et al 1974;Pfuderer et al 1974;Solomon 1977) should not be overlooked as it is plausible that such factors could also act to regulate fish GH, during crowding.…”
Section: Crowding Stressmentioning
confidence: 98%
“…Whilst it is too early to draw any firm conclusions as to the physiological importance of elevated GH during crowding stress it is possible that elevations in GH is a short term protective response against limited oxygen availability during crowding stress. In addition, the role and importance of ''crowding factors'' that are chemical agents (pheromones) known to adversely affect growth of fish (Francis et al 1974;Pfuderer et al 1974;Solomon 1977) should not be overlooked as it is plausible that such factors could also act to regulate fish GH, during crowding.…”
Section: Crowding Stressmentioning
confidence: 98%
“…). Previous studies have shown that several factors led to individual growth variation in animals, including environmental factors (Seymour ; Jobling & Baardvik ), social interaction factors (Jobling & Baardvik ; Sloman, Gilmour, Taylor & Metcalfe ), genetic factors (Wang, Hayward & Noltie ; Qian, Cui, Xie, Lei, Xiong & Yang ) and chemical mediator factors (Yu & Perlmutter ; Pfuderer, Willims & Francis).…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach has not been successful for hazard assessment primarily because there is a lack of correspondence between the physiological-biochemical endpoints and whole-animal responses (3)(4)(5) the use of physiological diagnostic tests to detect xenobiotics has provided limited utility in aquatic toxicology, as reviewed by Klaverkamp (1) on the cardiodepressor activity of phthalic acid esters (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%